Postinjection Muscle Fibrosis from Lupron. (25th May 2015) - Everest, Erica; Tsilianidis, Laurie A.; Raissouni, Nouhad; Ballock, Tracy; Blatnik, Terra; Haider, Anzar; Rogers, Douglas G.; Schweiger, B. Michelle
Abstract : We describe the case of a 6.5-year-old girl with central precocious puberty (CPP), which signifies the onset of secondary sexual characteristics before the age of eight in females and the age of nine in males as a result of stimulation of the hypothalamic-pituitary-gonadal axis. Her case is likely related to her adoption, as children who are adopted internationally have much higher rates of CPP. She had left breast development at Tanner Stage 2, adult body odor, and mildly advanced bone age. In order to halt puberty and maximize adult height, she was prescribed a gonadotropin releasing hormone analog, the first line treatment for CPP. She was administered Lupron (leuprolide acetate) Depot-Ped (3 months) intramuscularly. After her second injection, she developed swelling and muscle pain at the injection site on her right thigh. She also reported an impaired ability to walk. She was diagnosed with muscle fibrosis. This is the first reported case of muscle fibrosis resulting from Lupron injection.